2007
DOI: 10.1007/s00359-007-0285-z
|View full text |Cite
|
Sign up to set email alerts
|

Tone and call responses of units in the auditory nerve and dorsal medullary nucleus of Xenopus laevis

Abstract: The clawed frog Xenopus laevis produces vocalizations consisting of distinct patterns of clicks.This study provides the first description of spontaneous, pure-tone and communication-signal evoked discharge properties of auditory nerve (n.VIII) fibers and dorsal medullary nucleus (DMN) cells in an obligatorily aquatic anuran. Responses of 297 n.VIII and 253 DMN units are analyzed for spontaneous rates (SR), frequency tuning, rate-intensity functions, and firing rate adaptation, with a view to how these basic ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 59 publications
4
14
0
Order By: Relevance
“…We detected no effect of subject size on thresholds, consistent with invasive recordings from the VIIIth nerve of frogs, which have not previously demonstrated an effect of subject size on average thresholds of fibers (Elliott et al, 2007; Frishkopf et al, 1968; Zakon and Wilczynski, 1988). Females generally had lower thresholds than males, an effect that was more pronounced for low and mid-frequencies.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We detected no effect of subject size on thresholds, consistent with invasive recordings from the VIIIth nerve of frogs, which have not previously demonstrated an effect of subject size on average thresholds of fibers (Elliott et al, 2007; Frishkopf et al, 1968; Zakon and Wilczynski, 1988). Females generally had lower thresholds than males, an effect that was more pronounced for low and mid-frequencies.…”
Section: Discussionsupporting
confidence: 90%
“…However, effect sizes indicated that the effect of sex plays a relatively minor role in determining thresholds relative to the effect of frequency. For many frog species, the frequency to which the BP is most sensitive is lower in females than males (Narins and Capranica, 1976; Wilczynski et al, 1992; Zakon and Wilczynski, 1988; but see Elliott et al, 2007). However, consistent with previous studies in green treefrogs (Miranda and Wilczynski, 2009b; Penna et al, 1992), we did not see any evidence for a difference in the frequencies to which males and females were most sensitive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the peak disc velocity of 0.3 mm s 21 Pa 21 measured in the present study is comparable to that of Xenopus, ranging from 0.05 to 0.25 mm s 21 Pa 21 [26]. Therefore, the sensitivity of the turtle to underwater sound is broadly comparable to the sensitivity of both Xenopus [24] and otophysine fish [25], allowing for differences in experimental design and the generally higher thresholds in ABR experiments (see below).…”
Section: Discussionsupporting
confidence: 57%
“…The pointed tip of a vibration probe was connected to a B&K 4810 vibration exciter and glued to the disc using a drop of tissue glue (Vetbond, WPI). The vibration of the probe was calibrated using a small accelerometer (B&K 4500-A) connected to a B&K 2635 charge amplifier (see further details of the stimulation in Elliott et al [24]). The red line shows model data of fish swimbladder vibrations in a sound field [19] for 0.5 ml volume.…”
Section: (G) Disc Vibrationmentioning
confidence: 99%